The Effect of Method Pedagogy and English Teaching Learning - Ikram Senen (Winaya Inspirasi Nusantara Foundation, 2024)
The end of the 20th century, methodology was no longer the determining factor of whether language teaching was successful or unsuccessful in mainstream settings. In the 1990s, some ELT practitioners, teachers and theorists expressed their unhappiness with approaches and techniques when the concept of method was questioned. The purpose of this study is to find out how methodology pedagogy affects English teaching strategies. This research was A literature study research methodology is used in this investigation. In a literary study, information is gathered through reading and taking notes, and then the information is processed using the predetermined concepts. and do a study of theories in order to identify a concept using the approach of classifying the theory and research into a concept after studying the categorical portion of the theory. The findings show that learning a language invites educators and learners to explore the vast and intriguing world of limitless opportunities. In order to travel a satisfying path for both teachers and learners in the post-method era, educators must be aware of specific ways in addition to the essential elements mentioned above. Teachers and students need to be active participants in the creation of knowledge as a result of the transition from method-based to post-method classroom practices. Teachers should encourage students to explore their identity, context, emotional and cognitive factors, and ELT methods, rather than dictating their actions. This approach allows for better decision-making and allows for repeatability in case of mistakes.